2016
DOI: 10.7554/elife.19809
|View full text |Cite
|
Sign up to set email alerts
|

TRIM28 regulates the nuclear accumulation and toxicity of both alpha-synuclein and tau

Abstract: Several neurodegenerative diseases are driven by the toxic gain-of-function of specific proteins within the brain. Elevated levels of alpha-synuclein (α-Syn) appear to drive neurotoxicity in Parkinson's disease (PD); neuronal accumulation of tau is a hallmark of Alzheimer's disease (AD); and their increased levels cause neurodegeneration in humans and model organisms. Despite the clinical differences between AD and PD, several lines of evidence suggest that α-Syn and tau overlap pathologically. The connections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
117
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(138 citation statements)
references
References 57 publications
10
117
0
2
Order By: Relevance
“…High-throughput screening approaches based on alternative splicing have been used in many studies [19,[33][34][35]. Compared to these methods, our screening system takes into account the role of RNA secondary structure on regulation of alternative splicing.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput screening approaches based on alternative splicing have been used in many studies [19,[33][34][35]. Compared to these methods, our screening system takes into account the role of RNA secondary structure on regulation of alternative splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Although no direct interaction between α-Syn and importin α was observed, the authors suggest the involvement of other proteins mediating complex formation. Another recent study reported the role of a tripartite motif-containing protein 28 (TRIM28) in stabilizing α-Syn in the neuronal nucleus [25]. TRIM28 contains an NLS sequence that interacts with various importin α subtypes, facilitating its nuclear import where it binds to chromatin [57, 58].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are discrepancies in the literature about the presence of α-Syn in the nuclei of healthy neurons, presumably due to varying sensitivity of the detection methods employed, there is more consistent evidence supporting its nuclear localization in PD-affected neurons [2325]. While the relative abundance of α-Syn in the nucleus versus cytoplasm in various cell types has not been thoroughly investigated, it appears that about 5–10% of α-Syn localizes to the nucleus in cultured neurons.…”
Section: Introductionmentioning
confidence: 99%
“… AbstractAlzheimer’s and Parkinson’s disease are late onset neurodegenerative diseases that will require therapy over decades to mitigate the effects of disease-driving proteins such tau and α-synuclein (α-Syn). We recently found that TRIM28 regulates the levels and toxicity of α-Syn and tau (Rousseaux et al, 2016), however, how TRIM28 regulates α-Syn and whether its chronic inhibition later in life is safe remained unknown. Here, we show that TRIM28 mediates the SUMOylation of α-Syn and tau, and that genetic suppression of Trim28 in adult mice is compatible with life.…”
mentioning
confidence: 99%